Perception of Nurses on the importance of the use of Individual Protection Equipment for Biological Risks in a Service of Mobile Urgency Care - Lopes Mafra, Denise Aparecida; Fonseca, Isabela Cristine; Xavier Viana, Juliana; Batista Santana, Júlio César; Pereira Silva, Mariana (O Mundo da Saúde, 2008)
This study had as its objective to perceive the importance for nurses of the use of individual protection equipment (IPE) related to biological risks in the work of advanced support in a mobile service of urgency care, and to identify the IPE’s used by nurses in the mobile service of urgency care of the city of Sete Lagoas. The study has a exploratory descriptive nature with qualitative analysis based in Bardin’s method. The established thematic units were: identifying the biological risks in the pre-hospital care; vulnerability of the professionals for the risk of occupational exposition in the pre-hospital attendance; perceiving the importance of the use of individual protection equipment; the nurse as a link in the promotion of health. Results show that nurses have conscience of the importance of the use of IEP’s, but they do not use them duly in their work practice, as is proven in the sample where one sees that 100% of them use gloves, boots and overalls, but only 41.6% use masks and only 16.6% use eyeglasses in all cases they care for.